Serum sTfR levels may indicate charge profiling of urinary r-hEPO in doping control - Nissen-Lie, G.; Birkeland, K.; Hemmersbach, P.; Skibeli, V. (Medicine & Science in Sports & Exercise, 2004)
Purpose: The aim of the study was to demonstrate whether changes in the charge pattern of urinary human erythropoietin (u-hEPO) from well-trained athletes before, during and after controlled administration of recombinant human EPO (r-hEPO) could be related to altered levels of hemoglobin (Hb), hematocrit (Hct), soluble transferrin receptor (sTfR) and maximal oxygen uptake ([latin capital V with dot above]O2max). Methods: Urinary samples from athletes in an EPO-receiving group and a control group were collected before, during and after r-hEPO administration. The samples were analyzed with respect to the charge pattern of hEPO by iso-electric focusing (IEF). Results: The charge of the u-hEPO variants shifted from an acidic to a more basic pattern after initiating r-hEPO administration. This shift appeared together with increased levels of sTfR, and appeared before increased levels of Hb, Hct and [latin capital V with dot above]O2max. Until three days after the last injection, the IEF profiles were similar to the charge profile of r-hEPO. Thereafter the levels of sTfR decreased and the charge profiles of the hEPO variants gradually became more acidic. In contrast, the levels of Hb, Hct and [latin capital V with dot above]O2max remained elevated for an extended period of time. Conclusion: A significant correlation was found between the relative amount of basic u-hEPO variants and the relative levels of sTfR, demonstrating that the relative levels of sTfR may be used as a marker to select urinary samples for further analysis of r-hEPO by IEF in routine doping control.